On the question of periodization training content and Paralympic athletes with disorders of the musculoskeletal system in the light of the general theory of sports training - Derkach, V.N.; Yedinak, G.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : To determine theoretically similar trends and differences in the periods of sports training athletes and Paralympic athletes with similar qualifications, without disabilities. Material : analyzed more than 80 references. Results : at present insufficiently developed periodization sports training many years to prepare athletes with disorders of the musculoskeletal system. Also - at the stage of maximum realization of individual empowerment athletes. This applies to the immediate preparation for the main competition. In the first case, periodization can be carried out on the basis of the classical theory. Also on stage, maximizing the individual capabilities. Need to adapt this theory to career achievements of athletes. Also, you must consider the disease. Conclusions : The main factors set differences training tools Paralympic athletes and physically healthy: increased attention to the psychological preparation for the Paralympics, inclusive education and sports training individualization programs already in the first stage of their training.